Broadband Spurious-Free Dynamic Range Expander for Microwave Photonic Links Based on Optical Distortion Control - Tianwei Jiang; Jianming Shang; Song Yu; Xinmeng Ye; Wanyi Gu (IEEE Photonics Journal, 2019)
A wideband spurious-free dynamic range (SFDR) expander that uses optical distortion control technique is proposed in this study for microwave photonic links. A third-order intermodulation distortion (IMD3), which is sensed by extracting the modulated optical carrier, will be monitored and attenuated adaptively by controlling the optical power injected into the photodetector. Therefore, the IMD3 can be suppressed below the noise floor (NF), and the SFDR can be expanded further. In addition, the sensing signal stems from the modulated optical carrier, which is independent of radio frequency. Thus, our system is essentially a broadband system whereby the dynamic range expander is applied to classical intensity modulation and direct detection microwave photonic link. Experimental results demonstrate that the SFDR is improved from 46.84 to 67.98 $\text{dB}/\text{Hz}^{2/3}$ with a $-$ 70 dBm noise power. The SFDR can even reach 150 $\text{dB}/\text{Hz}^{2/3}$ with a bandwidth of 36 GHz with a 1 Hz NF.